Fondasi Ontologi Mullȃ Sadrȃ: Sebuah Tinjauan Filsafat - Arsyad Arsyad (Budapest International Research and Critics University, 2019)
Because a movement is an achievement of new actuality and perfection through motion, every movement is inevitably a strengthening process and causes the movement of something more perfect. Here we need to distinguish two points, one, the process of refinement of a motion and the other is the process of refinement of a moving subject. The moving agent can be constant reaching perfection through movement but the speed of the process can be that the speed of the improvement process increases or decreases or remains. Constant speed and deceleration do not conflict with the process of refinement in a movement. Examples of the process of moving an apple to be sweeter speed more sweetness decreases but still at each time sweeter than before even though the change is slowing down. Consequently, assuming that in a motion, the motion causes a refinement process for the moving agent does not conflict with assuming a reduced speed of the process